Joint investigation of strain partitioning and chemical partitioning in ferrite-containing TRIP-assisted steels. (March 2020) - Tan, Xiaodong; Ponge, Dirk; Lu, Wenjun; Xu, Yunbo; He, Huansheng; Yan, Jun; Wu, Di; Raabe, Dierk
Abstract: We applied two types of hot-rolling direct quenching and partitioning (HDQ&P) schemes to a low-C low-Si Al-added steel and obtained two ferrite-containing TRIP-assisted steels with different hard matrix structures, viz, martensite or bainite. Using quasi in-situ tensile tests combined with high-resolution electron back-scattered diffraction (EBSD) and microscopic digital image correlation (µ-DIC) analysis, we quantitatively investigated the TRIP effect and strain partitioning in the two steels and explored the influence of the strain partitioning between the soft and hard matrix structures on the TRIP effect. We also performed an atomic-scale analysis of the carbon partitioning among the different phases using atom probe tomography (APT). The results show that the strain mainly localizes in the ferrite in both types of materials. For the steel with a martensitic hard-matrix, a strong strain contrast exists between ferrite and martensite, with the local strain difference reaching up to about 75% at a global strain of 12.5%. Strain localization bands initiated in the ferrite rarely cross the ferrite/martensite interfaces. The low local strain (2%–10%) in the martensite regions leads to a slight TRIP effect with a transformation ratio of the retained austenite of about 7.5%. However, for the steel with bainitic matrix, the ferrite and bainite undergo more homogeneous strain partitioning, with an average local strain in ferrite and bainite of 15% and 8%, respectively, at a global strain of 12.5%. The strain localization bands originating in the ferrite can cross the ferrite/bainite (F/B) interfaces and increase the local strain in the bainite regions, resulting in an efficient TRIP effect. In that case the transformation ratio of the retained austenite is about 41%. The lower hardness difference between the ferrite and bainite of about 178 HV, compared with that between the ferrite and martensite of about 256 HV, leads to a lower strain contrast at the ferrite/bainite interfaces, thus retarding interfacial fracture. Further microstructure design for TRIP effect optimization should particularly focus on adjusting the strength contrast among the matrix structures and tuning strain partitioning to enhance the local strain partitioning into the retained austenite. Graphical abstract: Image, graphical abstract